Aspectos clínico-epidemiológicos de mulheres HIV positivo na URE-MIA/Belém-Pa. - COSTA, Diana Fiel da (2022)
INTRODUCTION: according to the World Health Organization, the control of HIV infection is the largest global health priority. The pandemic reaches every year more women, who in 2009 were 51% of the total number of carriers of the virus. In Brazil, over 54000 pregnant women were infected from 2000 until 6/30/2010. The northern region was the least suffered, however the State of Pará was the most recorded cases of infection in the region. OBJECTIVES: the overall objective of this study was to know the clinical epidemiological aspects-HIV positive women on URE-MIA/Belém-PA (Unidade de Referência Materno Infantil e Adolescente). The specific objectives were to describe the demographic aspects of the sample; check the prevalence of prenatal and if this was complete or not; note the most common form of exposure to HIV among patients; verify that the time was done the diagnosis of infection, in relation to pregnancy and childbirth; note the prevalence of use of antiretroviral therapy (ART), as well as conducting additional tests (CD4 and viral load) during pregnancy and childbirth; identify the major obstetric complications and the most common type of childbirth in the population of the study; compare the data obtained in the survey with what is advocated by the Ministry of Health (MOH) and draw up a protocol of admission service for HIV + pregnant women for prenatal performing in URE-MIA. METHODS: this is a transversal type research, primarily descriptive, performed with HIV positive women who have had children registered in infectious and parasitic diseases (DIP) of URE-MIA/Belém-PA, in the period of January 2008 to January 2010, for diagnostic research or monitoring of HIV infection. The collection of data was done through the medical records of children by result search protocol. Were considered qualitative and quantitative variables pertaining only to mothers, including socioeconomic data, form of contagion, antenatal screening, diagnosis, treatment, obstetric complications and childbirth. RESULTS: between 278 patients who make up the sample, it was found that most were aged 20 to 29 years, declared himself drab, attended the incomplete or complete elementary school, was home and founded the town of Belém; more than 90% prenatal held, but only 35.3% of these were full; the most common route of exposure was the sexual; 61.5% have made use of ART in pregnancy (only 3.6% of these as advocated by MOH) and 72.3% in childbirth (60.4% of these as recommended by MOH); 37.8% additional examinations were held in gestation and 5% in childbirth; 36% have obstetrical complications, the most common being threatened abortion (14%); the main route of childbirth was elective caesarean section (40%). CONCLUSION: there is still great deficiencies in coverage and prenatal follow-up of HIV positive patients in the State of Pará, need urgently greater professional training to meet this audience, adapting the recommendations of MOH since the amount of prenatal consultations, to diagnostics, treatment and type of childbirth in these cases.